Challenging Gameplay and Its Impact on Player Motivation in Gaming - Wibowo, Tony; Hardiwinata, Harley (UNIVERSITAS STEKOM, 2023)
The Video Game Industry is a subsidiary of the entertainment industry that is still growing. Video Games come in different genres and have unique experiences for every player. One of those unique games is the souls-like genre. The souls-like genre is games designed with a high difficulty level, with a dedicated fanbase that loves games with these genres. In this research, we would like to conduct research about Challenging Gameplay and Its Impact on Player Motivation in Gaming. In this research we used the experimental method to observe players’ reaction during the experiment and followed up with an interview. This experiment's result shows that participants who experience setbacks & defeat multiple times still show interest towards playing a game that has challenging gameplay outside of this experiment.